Meta-analysis of the efficacy of melatonin implants for improving reproductive performance in sheep - Palacin, I.; Forcada, F.; Abecia, J. A. (Spanish Journal of Agricultural Research, 2011)
To evaluate the efficacy of melatonin implants on increasing the production of lambs, a meta-analysis was performed based on the results of 139 experiments carried out in Spain and published in 56 scientific publications or conference proceedings. To assess the effects on fertility, the relative risk (RR) was calculated and, in the case of prolificacy and fecundity, the analysis was based on raw mean difference (D) and the standardized difference between means (d) and their corresponding confidence intervals. In addition, the experiments were stratified by the productive aptitude of the flocks, breed, time of year, and age. For fertility, the mean RR was 1.29, which indicated that the treatment with melatonin increased significantly (by 29%) the probability of pregnancy. For prolificacy, overall D was 0.08 (d = 0.9089); i.e., the groups treated with melatonin increased their litter size by 0.08 lambs/lambing relative to the control groups. Ultimately, treatment with melatonin increased fecundity significantly (0.25 extra lambs/ewe treated) (d = 6.3188), and this trend was evident in all of the stratified datasets. In all cases, there was significant (p < 0.001) heterogeneity and bias. In conclusion, in Spain, melatonin implants had a significant effect on the probability that a ewe became pregnant, increased the number of lambs born per lambing, which ultimately increased the number of lambs born per treated ewe. In addition to confirm the results of previous descriptive reviews in the scientific literature, the metaanalysis made use of a statistical tool that synthesizes and estimates more precisely the effect of this hormone on sheep reproduction.